Analisis Unjuk kerja Jaringan Microcell LTE Berdasarkan Variasi Level Modulasi - Shafira Fajrin Arumsidi; Anggun Fitrian Isnawati; Ade Wahyudin (AITI, 2019)
The development of telecommunications technology continues to increase, especially in the use of cellular communication networks. Users of cellular networks today need high-speed communication to be able to enjoy the facilities offered such as streaming video, web browsing, e-mail and others. With the current increase in user capacity, it causes a lot of interference. Therefore, the use of modulation techniques needs to be considered. To find out the proper use of modulation, in accordance with the conditions of the region and the network used, this study examines the performance of variations in modulation levels, namely QPSK, 16QAM, 64QAM and 256QAM. The parameters measured in this study include RSRP, CINR, BER, user connected and throughput. Based on the coverage by RSRP simulation results, it was found that the RSRP did not change because the power signal will always adjust to any use of the modulation level. For coverage by CINR obtained to obtain a higher rate value, a higher CINR value is needed and for coverage by BER parameters, BER does not affect the bit per symbol carried by each modulation, only affects the different types of modulation. Meanwhile, in the capacity by Throughput parameter, QPSK modulation produces the lowest average throughput value of 14.01 Mbps followed by 16QAM 21.58 Mbps 64QAM 28.6 Mbps and 256QAM 33.87 Mbps. In addition, for the capacity by user connected parameters all connected users on all modulation used will produce 100% for capacity by user connected.